Study of differences in presentation, risk factors and management in diabetic and nondiabetic patients with acute coronary syndrome - Krishna Kumar Sharma; Mukul Mathur; Sailesh Lodha; Surendra Kumar Sharma; Niharika Sharma; Rajeev Gupta (Indian Journal of Endocrinology and Metabolism, 2016)
Objectives: To compare clinical characteristics, treatment, and utilization of evidence-based medicines at discharge from hospital in acute coronary syndrome (ACS) patients with or without diabetes at a tertiary care cardiac center in India. Methods: We performed an observational study in consecutive patients discharged following management of ACS. We obtained demographic details, comorbid conditions, and cardiovascular risk factors, physical and biochemical parameters, and management. Descriptive statistics are reported. Results: We enrolled 100 patients (diabetics = 28) with mean age of 59.0 ± 10.8 years (diabetics 59.3 ± 11.6, nondiabetics 58.9 ± 8.5). Forty-nine patients had ST-elevation myocardial infarction (STEMI) (diabetics = 14, 28.7%) while 51 had nonSTEMI/unstable angina (diabetics = 14, 27.4%) (P = nonsignificant). Among diabetics versus nondiabetics there was greater prevalence (%) of hypertension (78.6% vs. 44.4%), obesity (25.0% vs. 8.3%), abdominal obesity (85.7% vs. 69.4%) and sedentary activity (89.2% vs. 77.8%), and lower prevalence of smoking/tobacco use (10.7% vs. 25.0%) (P < 0.05). In STEMI patients 28 (57.1%) were thrombolysed (diabetes 17.8% vs. 31.9%), percutaneous coronary interventions (PCI) was in 67.8% diabetics versus 84.7% nondiabetics and coronary bypass surgery in 21.4% versus 8.3%. At discharge, in diabetics versus nondiabetics, there was similar use of angiotensin converting enzyme inhibitors (67.9% vs. 69.4%) and statins (100.0% vs. 98.6%) while use of dual antiplatelet therapy (85.7% vs. 95.8%) and beta-blockers (64.3% vs. 73.6%) was lower (P < 0.05). Conclusions: Diabetic patients with ACS have greater prevalence of cardiometabolic risk factors (obesity, abdominal obesity, and hypertension) as compared to nondiabetic patients. Less diabetic patients undergo PCIs and receive lesser dual anti-platelet therapy and beta-blockers.